2013
DOI: 10.1007/s12281-013-0148-8
|View full text |Cite
|
Sign up to set email alerts
|

Filamentous Basidiomycetes in the Clinical Laboratory

Abstract: Filamentous basidiomycetes are difficult to identify in the clinical laboratory, mostly due to lack of sporulation, and their role as agents of fungal infection can be difficult to assess. More cases of infection with these agents are being reported as more laboratories gain proficiency with the recognition of their subtle morphologic features and the use of DNA-based methods for identification. Most infections occur in the respiratory tract and sinuses, although brain infection has been reported. Susceptibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 35 publications
1
26
0
Order By: Relevance
“…No published breakpoints and no standardised methods are available for the antifungal susceptibility testing of FB, however, basidiomycetes are usually intrinsically resistant to echinocandins. In general, low MICs are reported for amphotericin B, itraconazole, posaconazole, voriconazole, and high MICs for fluconazole, and flucytosine . MICs determined for both T. polyzona isolates were consistent with these observations.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…No published breakpoints and no standardised methods are available for the antifungal susceptibility testing of FB, however, basidiomycetes are usually intrinsically resistant to echinocandins. In general, low MICs are reported for amphotericin B, itraconazole, posaconazole, voriconazole, and high MICs for fluconazole, and flucytosine . MICs determined for both T. polyzona isolates were consistent with these observations.…”
Section: Discussionsupporting
confidence: 72%
“…The role of basidiomycete in diseases is certainly focused on cryptococcal infections, but FB, mainly Schizophyllum species, Hormographiella aspergillata, Ceriporia lacerata have been recently recognised as agents of human diseases . According to Chowdhary review, FB infections are principally reported in Japan (43%), and India (26%), and have been described in a large spectrum of diseases ranging from hypersensitivity to invasive fungal infections . T. polyzona (syn.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that echinocandins have been reported to be ineffective against clinically relevant basidiomycetes (67, 68), our discrepant results might be due to variations in the methods used (variations in incubation times, methods of preparation of the inoculum with hyphal fragments, etc.). Since there is no standardized method for antifungal susceptibility testing of filamentous basidiomycetes and nonsporulating fungi (68), studies often modify the CLSI protocol (31,34) in an attempt to obtain reproducible results, as in our case. Therefore, before standardization of these protocols, interlaboratory results cannot be properly compared.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of filamentous basidiomycetes as agents of invasive and allergic disease has increased in the past few years (2)(3)(4)(5). It is emphasized that due to the small number of samples tested in our study, it was difficult to demonstrate the efficacy of oral itraconazole in cases of ABPM due to S. commune.…”
mentioning
confidence: 80%